Literature Review: Threat of Artificial Intelligence (Ai) Cyber Attacks on Data Security - Apriansyah, Ferryma Arba; Ujianto, Erik Iman Heri; Rianto, Rianto (Peneliti.net, 2024)
The purpose of this study is to present an overview of the approaches and areas of concentration in data security identification. The report analyzes AI cyberattacks on Indonesian data security through a review of the literature. In order to find relevant papers, search terms like